Fibroblast behavior after titanium surfaces exposure - Matteo Danza; Ilaria Zollino; Valentina Candotto; Francesca Cura; Francesco Carinci (Wolters Kluwer Medknow Publications, 2012)
Background: The main requirements for a good material are its ability to promote attraction and adhesion of bone precursor cells and their proliferation and differentiation. Different biocompatible materials are currently employed as scaffold. Among these, titanium is considered a "gold standard" because of its biocompatibility and good corrosion resistance. Materials and Methods: The aim of this work was to compare two different AoN titanium layers (GR4 and GR5) to investigate which one had a greater osteoconductive power using human fibroblasts (HFb) culture at two different time-points. The expression levels of some adhesion and traction-resistance related genes (COL11A1, COL2A1, COL9A1, DSP, ELN, HAS1, and TFRC) were analyzed using real time reverse transcription-polymerase chain reaction. Results: After 7 days of treatment with TiA 4GR, the only two up-regulated genes were COL2A1 and DSP. After 15 days of treatment, none of genes over expressed. Conclusion: Our preliminary results suggest that neither AoN 4GR nor AoN 5GR are able to promote the production of protein involved in cell-cell and cell-matrix adhesion and in stress-resistance, required for a good outcome in dental implantology.